Kinematics Analysis and Experimental Validation for a Hybrid Machining Unit with Redundantly Actuated Parallel Mechanism - Jun Zhang; Yufei Bao; Hanliang Fang; Jirui Diao (Jixie chuandong)
A novel 5-DOF hybrid machining unit is designed and its kinematics is analyzed， in which a 2UPR&2RPS redundantly actuated parallel mechanism is acting as the spindle head. Firstly， the degree of freedom of proposed hybrid machining unit is analyzed based on the screw theory， it is proved that it has two rotational and three translational （2R3T） motion abilities. Secondly， a kinematics model of the hybrid machining unit is established by means of space vector， the analytical inverse and forward position formulations are derived. Thirdly， the workspace of the hybrid machining unit is predicted based on the hierarchical search idea， the distribution of the 5-axis reachable workspace is given. Finally， a set of machining tests are conducted on a laboratory prototype to experimentally validate the correctness of aforementioned kinematic analyses.